Persepsi Konsumen Terhadap Keputusan Pembelian Di Bukalapak - Gandhy, Abel; Karmila, Jelin Tria; Pakpahan, Reynaldy; Hardini, Sri Yuniati P.K (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The development of information technology is increasing rapidly. The internet is widely used in various ways, one of which is e-commerce applications for online shopping. One of the popular e-commerce in Indonesia is Bukalapak. The purpose of this study was to determine consumer perceptions of purchasing decisions at Bukalapak. The data used in this study were obtained by distributing questionnaires. The number of respondents in this study were 100 people. Data analysis techniques using multiple regression analysis consists of simultaneous tests and partial tests. The results in this study showe that the independent variables consisting of shopping experience, service quality, product perception and perceived risk partially influence purchasing decisions. Simultaneously the consumer perception variable has a significant effect on purchasing decisions. Service quality variable has a strong influence on purchasing decisions. For this reason, Bukalapak companies need to improve online services so consumers can make decisions and buy from Bukalapak. Companies are expected to work with online payment media and delivery services that can be trusted.